1989
DOI: 10.1182/blood.v73.4.1033.bloodjournal7341033
|View full text |Cite
|
Sign up to set email alerts
|

Nonhematopoietic tumor cells express functional GM-CSF receptors

Abstract: Human granulocyte-macrophage colony-stimulating factor (GM-CSF) stimulates the colony growth of myeloid progenitors in semisolid media, and enhances the function of mature effector cells, including neutrophils, monocytes, and eosinophils. Small cell carcinoma lines (SCCL) have properties of amine precursor uptake and decarboxylation (APUD) cells and express high levels of the enzyme, L-aromatic amino acid decarboxylase. We looked for possible expression of GM-CSF receptors on nonhematopoietic cells and found s… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

1
16
1

Year Published

1990
1990
2012
2012

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 24 publications
(18 citation statements)
references
References 0 publications
1
16
1
Order By: Relevance
“…This study revealed that 9 of 35 (26%) nonhematopoietic tumor cell lines expressed GM-CSF receptors. Although previous reports described that GM-CSF receptors were expressed on SCLC cells, but not on non-SCLC cells (Baldwin et al, 1989), we did not detect the significant binding of GM-CSF to SCLC cells which we tested. In contrast, GM-CSF receptors were expressed on 3 of 9 non-SCLC cells (Table 1).…”
Section: Resultscontrasting
confidence: 93%
See 3 more Smart Citations
“…This study revealed that 9 of 35 (26%) nonhematopoietic tumor cell lines expressed GM-CSF receptors. Although previous reports described that GM-CSF receptors were expressed on SCLC cells, but not on non-SCLC cells (Baldwin et al, 1989), we did not detect the significant binding of GM-CSF to SCLC cells which we tested. In contrast, GM-CSF receptors were expressed on 3 of 9 non-SCLC cells (Table 1).…”
Section: Resultscontrasting
confidence: 93%
“…Present results indicated that GM-CSF receptors are frequently expressed on non-SCLC cells rather than SCLC cells. The previous report described that only SCLC cells expressed GM-CSF receptors (Baldwin et al, 1989), and no report described the distribution of GM-CSF receptors on non-SCLC cells. The difference between previous reports and present one may be due to instability of cellular characteristics of lung cancer including surface receptor molecules.…”
Section: Discussionmentioning
confidence: 97%
See 2 more Smart Citations
“…Several studies have suggested that GM-CSF responsiveness may not be limited to hematopoietic lineages (26)(27)(28)(29)(30)(31). Endothelial cells (EC) respond to GM-CSF (32,33) and express both GM-CSFR subunits (17,33).…”
mentioning
confidence: 99%